Virtual Art Innovations for Maintaining the Existence of Riau Malay Culture - Rizkiki Utami; Andra Wahdini; Augusto Prastyo Yoshuhiro Prakoso (Gelar : Jurnal Seni Budaya, 2021)
AbstractThe COVID-19 pandemic affects all aspects, including cultural arts. Cultural arts have an important role in human civilization as a result of thoughts and traditions from ancestors. The existence of the cultural arts of Malay Riau is decreased during the pandemic. All cultural arts activities have been shifted from the offline stage to the online stage so that the efforts to inherit and develop the cultural arts of Malay Riau are hampered. This research aims to determine the differences in the existence of Malay Riau cultural arts before and after the pandemic in Riau students at the Malay Riau Cultural Unit, Bandung Institute of Technology (UKMR ITB) and in Riau people in general. This research also aims to gather the opinions from Riau students and Riau people about innovations to inherit the Malay Riau cultural arts during the pandemic. The methods which are used in this research to gather the data: study literature, interviews, and questionnaires. Based on this research, Malay Riau Cultural Unit has made an innovation to inherit the values of Malay Riau cultural arts through making cultural archives so that the inheritance of traditions can be carried out, even though the pandemic is still undergoing. Through this research, we hope that the existence of Malay Riau cultural arts can be maintained through continuous innovation, especially in Riau students at the Malay Riau Cultural Unit and in the Riau people.Keywords: Cultural arts; Malay Riau; Existence, pandemic; Innovation